KONSTRUKSI HUKUM PERBUATAN MELAWAN HUKUM BERUPA PENCEMARAN NAMA BAIK YANG DILAKUKAN MELALUI INTERNET BERDASARKAN UNDANG-UNDANG 11 TAHUN 2008 TENTANG ITE (INFORMASI DAN TRANSAKSI ELEKTRONIK) - , Nurmalia Ihsana ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to determine the elements of defamation is done through the internet and how the legal protections of defamation actions are regulated in ACT Number 11 OF 2008 in ITE (Information and Electronic Transactions). Research using a normative juridical approach by focusing research on primary data with field research and approach through the principles of law and comparative law. This research relies on library materials as the primary data which consist of primary legal materials, secondary and tertiary. The results showed that the Construction defamation lawsuit still generate multiple interpretations because of the element of defamation that exists in Article 27 (3) of the Act ITE still refer to the provisions contained in Article 310 and Article 311 of the Criminal Code, while the penalty provisions for defamation actions the actors are very much different between the sanctions stipulated in the Penal Code with the provision of the Act ITE and arrests, which can be given to the actors still have to be revisited in a way tailored to the type of act of murder. Because the sentence should take effect only deterrent to the perpetrators. Legal protection that can be done by the victim are a civil lawsuit, criminal reports and completion of arbitration claims that may be requested is material and immaterial compensation and apology from the perpetrators who may be given in public. In terms of choice of legal settlement of defamation actions should be examined carefully because of honor and good name are the subjective self of each, and the views of the original problem.